1993
DOI: 10.1176/ajp.150.5.801
|View full text |Cite
|
Sign up to set email alerts
|

Missed psychiatric appointments: who returns and who stays away

Abstract: Most patients quickly reschedule missed appointments, and those in more intensive treatments miss fewer appointments. Missed appointments for initial evaluation are not rescheduled most often. Patients in ongoing treatment who do not return may have histories of noncompliance with treatment. The high rate of rescheduling suggests that follow-up of patients who miss appointments should be a clinical decision rather than a routine policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…Available literatures provide a non-compliance rate of (12-60%). [713] In the present study, non compliance is 41.9%. The mean age (32.36 ± 7.59) of patients who were non-compliant is lower than that of mean age of patients who were compliant (37.69 ± 11.59).…”
Section: Discussionmentioning
confidence: 47%
“…Available literatures provide a non-compliance rate of (12-60%). [713] In the present study, non compliance is 41.9%. The mean age (32.36 ± 7.59) of patients who were non-compliant is lower than that of mean age of patients who were compliant (37.69 ± 11.59).…”
Section: Discussionmentioning
confidence: 47%
“…As reported in earlier studies, in this study too, substance use was significantly associated with noncompliance. [1642]…”
Section: Discussionmentioning
confidence: 99%
“…[15] It is also reported that there is high prevalence of substance abuse in schizophrenia in noncompliant patients. [16] Other contributing factors are low priority accorded to health by patients and their caregivers, higher importance to economic activities, tendency to deal with problems only when they become acute and high emphasis on doctors’ exclusive role in alleviating symptoms of the patient. [17] Noncompliance is strongly related to clinical outcomes such as relapse, rehospitalization, and suicide attempts in schizophrenia[18] and bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…There are various challenges in continuing care in mental health-care settings, among which missed appointments (MA) are a common occurrence in outpatient care settings,[12] yet little is known about the reasons for MA, especially in the Indian population. Follow-up studies from around the world including India[3456789101112] show that 16–60% of patients will not follow up in spite of the need for further treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[3456789101112] Most common reason for MA in the studies is patient errors such as forgetting or oversleeping followed by social stigma, financial reasons, logistics, or getting the date wrong. [121112] The use of mobile phones has grown exponentially, especially in India. Mobile phones have been used to improve health outcomes in number of studies but its role to improve follow-up in psychiatry is yet to be established.…”
Section: Introductionmentioning
confidence: 99%